Struktur Komunitas Makrobentos Pada Kawasan Budidaya dan Non Budidaya Di Pulau Tembelas, Kabupaten Karimun Kepuluan Riau - Prahmawaty, Raden Faradhiva; Putro, Sapto punomo; Hariyati, Riche (Bioma : Berkala Ilmiah Biologi, 2018)
The macrobenthos community structure of living organisms in aquatic base, can function as a bioindicator of changes in aquatic environments, are sensitive to any disturbance of environmental changes within a waters. This research aims to determine the effect of different structures of macrobenthos communities in the cultivation environment and noncultivation environment. The research was conducted for 4 months on Tembelas island in 2 areas that were monoculture cultivation and reference area. Abiotic data obtained were substrate grain analysis and total organic analysis of carbon and nitrogen, as well as abiotic environmental parameters such as temperature, pH, salinity and dissolved oxygen. The biotic data obtained in the form of macrobenthos species that were found and the amount in the area was then calculated using non parametric index that were the level of diversity, eveness and abundance, and T test. The identification result showed the number of species found as many as 24 species in the monoculture location and 42 species at the reference location. Dominant species found in monoculture locations were Costoanachis sp and Anodontia sp. dominant species found in the reference sites were Nuculana sp and Ellobium sp. Shannon-Wiener (H') diversity index value at monoculture location was 2,43, while reference index value index had bigger index value 2,83. The abiotic quality of monoculture and reference aquatic environments was categorized as good. Based on the result of the research, it can be concluded that reference environment had better macrobenthos diversity value than monoculture environment.Â Keywords: Makrobenthos, Monoculture, Reference Environment